Meninjau Kembali Pemikiran Nurcholish Madjid: Neo-Republikanisme Islam dan Kewargaan Demokratis di Indonesia - Bunta, Abd. Firman; Hasmawati; Djumat, Irwan (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
The rise of conservatism and identity polarization underscores the urgency of constructing religious discourse compatible with inclusive democracy. Nurcholish Madjid's thought offers a synthesis of Islamic moral principles and modern democratic values. This study employs qualitative library research with a hermeneutic content-analysis approach, drawing primarily on Nurcholish's works and relevant secondary literature. The findings reveal that his framework constitutes an Islamic neo-republicanism characterized by freedom as non-domination, civic participation, deliberation, and public ethics. Unlike many neo-modernist Muslim intellectuals who remain at the level of normative pluralism, Nurcholish advances a more substantive conception of political freedom. At the core of his thought lies the rejection of all forms of domination - whether symbolic or through religious formalism - and the insistence that both state and religion must secure inclusive spaces that guarantee equality for all citizens. This study concludes that Nurcholish Madjid's Islamic neo-republicanism is not merely a reinterpretation of pluralism, but rather a paradigm of democratic citizenship grounded in progressive Islamic ethics, offering a substantive conceptual framework for strengthening democratic life in Indonesia.